Efficiency Analysis Using The DEA (Data Envelopment Analysis) Method at Fish Auction Place in the City of Sibolga - Siregar, Indra Mahdan; Sukardi, Sukardi; Rujiman, Rujiman (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The research aims to determine the level of TPI efficiency using the DEA (Data Envelopment Analysis) method in the research area. The sampling technique used was purposive sampling with judgment. The data source used is secondary data collected through Annual Reports. Data collection was carried out in two ways, namely documentation and literature. The analysis method used is the DEA (Data Envelopment Analysis) method with indicators for the input variables used: floor area, base length, number of boats, number of baskets, number of fishing gear, and indicators for the output variables used: Total production. The results of the research are the efficiency of the Sibolga Fish Auction Place which has a score of 100% in January, February, March, and April. In November it gets an efficiency score of 92.07%. This efficiency is at a high level of efficiency because it gets a value of > 81%. while efficiency in May, June, July, August, September, October, and December is 60-80%. This efficiency is at a medium efficiency level because it gets a value of 60-80%. Fish Auction Places in Sibolga that have achieved high efficiency in January, February, March, April, and November have been able to utilize input optimally to manage output. Meanwhile, moderate efficiency was shown in May, June, July, August, September, October, and December. It is hoped that we can utilize input optimally to manage output.